Invasive Fusarium solani infection diagnosed by traditional microbial detection methods and metagenomic next-generation sequencing in a pediatric patient: a case report and literature review - Ling, Jiaji; Liang, Liting; Liu, Xingxin; Wu, Wenjing; Yan, Ziyi; Zhou, Wei; Jiang, Yongmei; Kuang, Linghan (Frontiers in Medicine, 2024)
Fusarium solani, as an opportunistic pathogen, can infect individuals with immunosuppression, neutropenia, hematopoietic stem cell transplantation (HSCT), or other high-risk factors, leading to invasive or localized infections. Particularly in patients following allogeneic HSCT, Fusarium solani is more likely to cause invasive or disseminated infections. This study focuses on a pediatric patient who underwent HSCT for severe aplastic anemia. Although initial blood cultures were negative, an abnormality was detected in the 1,3-β-D-glucan test (G test) post-transplantation. To determine the causative agent, blood samples were subjected to metagenomic next-generation sequencing (mNGS) and blood cultures simultaneously. Surprisingly, the results of MALDI-TOF MS and mNGS differed slightly, with mNGS identifying Nectria haematonectria, while MALDI-TOF MS based on culture showed Fusarium solani. To clarify the results, Sanger sequencing was performed for further detection, and the results were consistent with those of MALDI-TOF MS. Since the accuracy of Sanger sequencing is higher than that of mNGS, the diagnosis was revised to invasive Fusarium solani infection. With advancements in technology, various detection methods for invasive fungi have been developed in recent years, such as mNGS, which has high sensitivity. While traditional methods may be time-consuming, they are important due to their high specificity. Therefore, in clinical practice, it is essential to utilize both traditional and novel detection methods in a complementary manner to enhance the diagnosis of invasive fungal infections.